Protirealistične teorije znanja - Klemenčič, Eva (Šolsko polje, 2013)
The article focuses on anti-realistic theories of knowledge and tries to introduce the different types of anti-realism. Anti-realistic theories of knowledge (or social constructivism as one of the anti-realistic type) do not accept the reality which is independent of us. If reality is not independent of us, therefore knowledge can not exist independently of us as well. Furthermore, this is one of the key ideas of social constructivism: knowledge is construction of reality. Although there are some differences between micro- and macro-social aspect of the construction of knowledge, however, both aspects underline the construction of knowledge (either more individual or more social aspects). For social constructivists, this is never merely a mapping of objective reality to which individuals and society have no impact.
Keywords: anti-realism; learning; učenje; znanje; constructivism; knowledge; protirealizem; theories of knowledge; konstruktivizem